(untitled) (Fiep Bulletin - online, 2016)
Every day children are subjected to sports programs in different contexts, such as clubs, parks, social projects and school physical education classes. Sports practices are part of everyday life. The language/culture of daily life, as the language of sports culture, delineates the life in society, where they seize tipificadores schemes that shape and determine attitudes and relationships. The objective was to analyze, from the perspective of the sociology of everyday life, the processes of socialization of the sport, identifying the actions and attitudes of resistance and transgressions of the children and adolescents in sports activities. We used the method of Sociology retrospective of Malik (2008), with criticism of memories of school and training delivered and also images of sporting practices as sources, interpreting data overlooked the behaviors of students. The results showed that the athletes have resistance and small transgressions behaviors that reveal discontent with the teaching and practice of sports and other interests. The research of everyday life proved way to understanding deviant behaviour in sport, unraveling relations and social orders, identifying outsiders sports practices.